FINANCIAL STATEMENTS OF ENTERPRISES IN MODERN ECONOMIC CONDITIONS: PROBLEMATIC ASPECTS AND PERSPECTIVES OF DEVELOPMENT - Царук, В. Ю. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Financial reporting is one of accounting system fundamental elements. The primary purpose of financial reporting is to provide users with accurate; complete; and unbiased information. Despite the reforms in the field of accounting; financial reporting in Ukraine; still does not meet the international standards. However; it is the international financial reporting standards that are the most effective tool for enhancing the transparency and comprehensibility of information that reveals the activities of business entities. Study of domestic enterprises financial statements problematic aspects in modern managing conditions and substantiation of financial statements development prospects are important. According to this purpose; we used a dialectical and systemic approaches to the study of problematic aspects of enterprises financial statements in modern economic conditions; abstract-logical method was used for theoretical generalizations and determination of financial statements development prospects. Adapting the domestic enterprises reporting to IFRS will increase the users confidencein financial statements and provide the transparency and accessibility of information; reduce risks for investors. Research of the problem aspects of financial statements is necessary for the formation of financial reporting further improvement and development trends in Ukraine. Proposed recommendations and suggestions will allow to generate new research areas in the field of theory and methodology of accounting; will also discover the perspectives of financial reporting and contribute to increased efficiency of accounting organization for domestic enterprises.